2012
DOI: 10.3329/ujzru.v30i0.10758
|View full text |Cite
|
Sign up to set email alerts
|

Occurence of ecto- and endo parasites in pigeon (Columba livia Linn.)

Abstract: DOI: http://dx.doi.org/10.3329/ujzru.v30i0.10758Univ. j. zool. Rajshahi Univ. Vol. 30, 2011 pp. 73-75

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 5 publications
0
19
1
Order By: Relevance
“…The observations of this study somewhat lower the report of Musa et al (2011). The higher prevalence of ecto-parasitic infections might be due to due to favorable climatic conditions as well as diversified topography of the sampled areas (combination of plane, hilly and coastal areas) which favors the growth and development of such ecto-parasites.…”
Section: Discussion Prevalence Of Ecto-parasitic Infestationscontrasting
confidence: 56%
“…The observations of this study somewhat lower the report of Musa et al (2011). The higher prevalence of ecto-parasitic infections might be due to due to favorable climatic conditions as well as diversified topography of the sampled areas (combination of plane, hilly and coastal areas) which favors the growth and development of such ecto-parasites.…”
Section: Discussion Prevalence Of Ecto-parasitic Infestationscontrasting
confidence: 56%
“…Interestingly, the louse species M. stramineus is found on at least eight host species from two different host orders (Brown, 1971;Dranzoa et al, 1999;Price et al, 2003;Musa et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…All four of these species are permanent obligate parasites that are found on Rock Pigeons (C. livia; Brown, 1971;Dranzoa et al, 1999;Price et al, 2003;Musa et al, 2011). Rock Pigeons are also parasitized by a hippoboscid fly (P. canariensis).…”
Section: Introductionmentioning
confidence: 99%
“…Echinoparyphium paraulum), Echinoparyphium recurvatum, Haplorchis pulimio, Brachylaima cribbi, Paratanaisia bragai, Hypoderaeum conoideum, and Catatropis verrucosa (2,3,7,8,10,17,19,20). This study is the first demonstration of the presence of E. revolutum in racing pigeons in Poland via a genetic approach employing the nad1 gene and 28S rDNA as genetic markers.…”
Section: Discussionmentioning
confidence: 87%
“…The presence of those flukes was described in three out of 255 mourning doves (Zenaida macroura) in the United States (1). Later studies confirmed the presence of that parasite in pigeons in India and Bangladesh (7,10). However, it was not reported whether the invasion caused any pathologic signs in the birds.…”
mentioning
confidence: 99%